Description and analysis of three Homo naledi incudes from the Dinaledi Chamber, Rising Star cave (South Africa). Issue 122 (September 2018) - Elliott, Marina C.; Quam, Rolf; Nalla, Shahed; de Ruiter, Darryl J.; Hawks, John; Berger, Lee R.
Abstract: This study describes three incudes recovered from the Dinaledi Chamber in the Rising Star cave system in South Africa. All three bones were recovered during sieving of excavated sediments and likely represent three Homo naledi individuals. Morphologically and metrically, the Dinaledi ossicles resemble those of chimpanzees and Paranthropus robustus more than they do later members of the genus Homo, and fall outside of the modern human range of variation in several dimensions. Despite this, when overall size is considered, the functional lengths in H. naledi and P. robustus are very similar to those predicted for a human with a similar-sized incus. In this sense, both taxa seem to show a relatively elongated functional length, distinguishing them from chimpanzees. The functional length in H. naledi is slightly longer in absolute terms than in P. robustus, suggesting H. naledi may already show a slight increase in functional length compared with early hominins. While H. naledi lacks the more open angle between the long and short processes found in modern humans, considered a derived feature within the genus Homo, the value in H. naledi is similar to that predicted for a hominoid with a similar-sized incus. Principal components analysis of size-standardized variables shows H. naledi falling outside of the recent human range of variation, but within the confidence ellipse for gorillas. Phylogenetic polarity is complicated by the absence of incus data from early members of the genus Homo, but the generally primitive nature of the H. naledi incudes is consistent with other primitive features of the species, such as the very small cranial capacity. These ossicles add significantly to the understanding of incus variation in hominins and provide important new data on the morphology and taxonomic affinities of H. naledi .